Ten Tips to Simplify the Spaghetti Wrist - Meals, Clifton G. (Plast Reconstr Surg Glob Open, 2018)
Hand surgeons refer to deep lacerations of the volar distal forearm as “spaghetti wrists.” Given that multiple tendons, vessels, and nerves often require repair, this injury may be intimidating. We review management of spaghetti wrists and summarize with 10 simplifying tips.